Low Self-Control and Cybercrime Victimization: An Examination of Indirect Effects Through Risky Online Behavior - Partin, Raymond D. (Crime & delinquency, 2022)
Research has established that individuals lower in self-control are at increased risk of offline criminal victimization due to their proclivity to engage in risky routine activities. While some studies have investigated whether a similar pattern is observed in the online context, additional inquiry into whether the link between low self-control and cybercrime victimization operates indirectly through risky online behavior is warranted given certain measurement and methodological limitations of prior research. Using original data collected on a sample of young adults, we find that the association between low self-control and a variety measure of cybercrime victimization operates entirely and indirectly through a variety measure of risky online behaviors. The implications of this finding for policy and programing are discussed.